Women´s experiences of menopause: A qualitative study among women in Soweto, South Africa - Sostina Spiwe Matina; Emily Mendenhall; Emmanuel Cohen (Taylor & Francis Group, 2024)
ABSTRACTWomen today are experiencing menopause for decades more than in previous generations. This 'change of life' is defined by an entire stage of physical, hormonal, and emotional changes that accompany menstrual irregularity and the cessation of fertility, although limited medical research has focused on it. Yet, the inevitability of menopause is universal for all human females around 50 years old. In this article, we conducted twenty-five 20-60 min semi-structured qualitative interviews. Most women marked menopause by fertility cessation and social transition to old age, pushing back against a medical framework of menopause that emphasises hormonal deficiency and becoming disordered. In contrast, women frame menopause as a natural process that contributes to a critical social role transition, which they perceive as deeply private in part because it is associated with a reduction in femininity, sexuality, and power. On the other hand, menopause was also described as a liberating process through which women no longer needed to purchase pads or manage blood loss. Recognising how women may perceive menopause not as a deficit or disorder but as a social role transition that has both costs and benefits is useful for medical practitioners when discussing clinical options.